Pengaruh E-service Quality, E-satisfaction Terhadap E-loyalty, Melalui E-trust Sebagai Variabel Mediasi pada Aplikasi Brins Mobile - Maghfiroh, Nova Wahyu; Badi'ah, Roudlotul (Forum Kerjasama Pendidikan Tinggi, 2025)
This research aims to analyze the influence of e-service quality and e-satisfaction on e-loyalty, with e-trust as amediating variable in the Brins Mobile appli cation. The problem discussed is how the quality of electronicservices and user satisfaction can influence application user loyalty. The method used in this research is aquantitative approach with data analysis using Partial Least Square (PLS), as well a s data collection throughquestionnaires involving 100 respondents using the Brins Mobile application. The research results show that e-service quality has a positive and significant effect on e-satisfaction, and e-satisfaction has a positive andsignificant effect on e-loyalty. In addition, e-trust is proven to mediate the relationship between e-service qualityand e-loyalty. Overall, this research found that e-service quality contributed 74.4% to e-satisfaction and 26.1%to e-loyalty. To improve the quality of electronic services on the Brins Mobile application, it is necessary tooptimize the user interface through lighting design, increase service speed so that the application runs smoothly, and personalize services to suit user needs. When it comes to satisfying user satisfaction, it is important to provide responsive customer service channels, offer rewards programs, and regularly conduct monitoring to obtain feedback. In addition, building trust can be done by strengthening data security, providing tra nsparent information, and maintaining consistent service quality.